A technological innovation systems analysis of the renewable energy technologies under the feed-in-tariff program. - Malonzo, Nur Ishmael H.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2015)
The Renewable Energy Act of 2008, through the National Renewable Energy Program (NREP), has increased the development of Renewable Energy sources (solar, hydro, wind, geothermal and biomass). Tax holidays and the Feed-in-Tariff (FIT) have encouraged this development. The FIT in particular is controversial as it compels electricity consumers to pay more in order to guarantee a fixed payment for the generation of Renewable Energy (RE) at rates that are currently more expensive than the average market rate for electricity. In the country at present the covered RE production constitutes a small percentage of total energy production. Consequently its immediate projected contribution to the electricity rate is still small. But this will increase as more energy producers are attracted by the incentives and the percentage of RE contribution grows. This research will analyze the local Technological Innovation System (TIS) for the core technology of each renewable energy resource covered in the FIT program. The goal is to identifying any potential pitfall and to find a way to foster design and development, and manufacturing capability build-up using the framework.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Renewable energy sources -- Law and legislation -- Philippines; Renewable energy sources; Technological innovations -- Philippines